Long‐term survival of pig‐to‐rhesus macaque renal xenografts is dependent on CD4 T cell depletion. Issue 8 (5th April 2019) - Kim, Steven C.; Mathews, David V.; Breeden, Cynthia P.; Higginbotham, Laura B.; Ladowski, Joseph; Martens, Gregory; Stephenson, Allison; Farris, Alton B.; Strobert, Elizabeth A.; Jenkins, Joe; Walters, Eric M.; Larsen, Christian P.; et al.
Abstract : The shortage of available organs remains the greatest barrier to expanding access to transplant. Despite advances in genetic editing and immunosuppression, survival in experimental models of kidney xenotransplant has generally been limited to <100 days. We found that pretransplant selection of recipients with low titers of anti‐pig antibodies significantly improved survival in a pig‐to–rhesus macaque kidney transplant model (6 days vs median survival time 235 days). Immunosuppression included transient pan–T cell depletion and an anti‐CD154–based maintenance regimen. Selective depletion of CD4 + T cells but not CD8 + T cells resulted in long‐term survival (median survival time >400 days vs 6 days). These studies suggested that CD4 + T cells may have a more prominent role in xenograft rejection compared with CD8 + T cells. Although animals that received selective depletion of CD8 + T cells showed signs of early cellular rejection (marked CD4 + infiltrates), animals receiving selective CD4 + depletion exhibited normal biopsy results until late, when signs of chronic antibody rejection were present. In vitro study results suggested that rhesus CD4 + T cells required the presence of SLA class II to mount an effective proliferative response. The combination of low pretransplant anti‐pig antibody and CD4 depletion resulted in consistent, long‐term xenograft survival. Abstract : CD4 T cell depletion is critical to long‐term (beyond 1 year) survival of pig‐to‐nonhuman primate kidney xenografts.